2014
DOI: 10.3389/fmars.2014.00035
|View full text |Cite
|
Sign up to set email alerts
|

Malettinin E, an antibacterial and antifungal tropolone produced by a marine Cladosporium strain

Abstract: The isolation and structure elucidation of malettinins A-C (1-3) along with the new malettinin E (4) are described. The compounds were produced by the fungus Cladosporium sp. strain KF501, which was isolated from the German Wadden Sea. The malettinins are built up of tropolone/dihydropyran ring structures linked to a furan ring. The structure elucidation of the isolated compounds was achieved by means of one-and two-dimensional NMR spectroscopy supported by mass and UV data. The relative configuration of 4 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
0
19
0
2
Order By: Relevance
“…KF525 [ 31 , 32 ], B. robillardoides LF550 [ 27 ], Cladosporium sp. KF501 [ 33 ], and Massariosphaeria typhicola KF970 [ 34 ]. A number of new compounds and their bioactivities from these studies were reported.…”
Section: New Metabolites From Marine Fungimentioning
confidence: 99%
See 3 more Smart Citations
“…KF525 [ 31 , 32 ], B. robillardoides LF550 [ 27 ], Cladosporium sp. KF501 [ 33 ], and Massariosphaeria typhicola KF970 [ 34 ]. A number of new compounds and their bioactivities from these studies were reported.…”
Section: New Metabolites From Marine Fungimentioning
confidence: 99%
“…colombiae . Hence, strain KF501 could be clearly identified as a member of the genus Cladosporium , but identification to the species level could not be achieved [ 33 ].…”
Section: New Metabolites From Marine Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…Among marine microorganisms, fungi play a crucial role, being a reservoir of biologically active secondary metabolites [4][5][6]. Recently, several new metabolites from marine fungi have been reported to display notable antibacterial activities [7][8][9]. Despite their proven biosynthetic potential, scientific research has not intensively focused on marine fungi for seeking new drugs [10].…”
Section: Introductionmentioning
confidence: 99%